Exploring the effects of conducting mindful compassion art-based therapy for dementia caregivers (MCAT-DC) online : barriers and moderators for effective online implementation - Kong, Jolene Ling (Nanyang Technological University, 2021)
Background: Dementia caregivers are facing significant stress and burden, exacerbated by the restrictive measures surrounding the COVID-19 pandemic. However, remote interventions providing psychological and holistic support to dementia caregivers are currently lacking in Singapore, and therapists are unconfident in online service delivery. Objective: This study aims to inform the provision of effective wellbeing e-therapy interventions for dementia caregivers that are acceptable to both the caregivers and the therapists implementing it. Thus, this study seeks to elucidate the perceived barriers and enabling factors via an examination of the lived experiences in implementing and receiving the implementation of online Mindfulness-Compassion Art-based Therapy for Dementia Caregivers (MCAT-DC). Methods: 7 intervention participants and 3 therapists participated in 4 weekly 2-hour sessions of online MCAT-DC. Weekly group discussions, and single-category focus groups held separately with the participants and therapists after the intervention were digitally recorded, transcribed, and analysed using thematic analysis. Results: Barriers and enabling factors were found across 4 main theme categories of session implementation, participant bonds, therapeutic e-alliance, and sustaining participation. Conclusion: These findings meet the urgent need of understanding the challenges of implementing online interventions for dementia caregivers, as well as observed mediators to improve current service provision. It also points to recommendations based on the results to aid in sustaining such services, which is poignant given the relative longevity of restrictive measures relating to COVID-19.